KAJIAN TATA KELOLA IT BERDASARKAN INDEKS KAMI PADA UNIVERSITAS PAKUAN BOGOR - Nur Hidayati (Paradigma, 2014)
Corporate governance of information technology is becoming a very important needs for the sake of the survival of an organization. IT governance practices at the University of Pakuan (UNPAK) Faculty of MIPA Bogor in particular has not been done optimally , which still require evaluation in it, this was to be one of the goals in this study. By using descriptive types of qualitative research and exploratory that  expected to know the condition of  IT governance is ongoing. Results of the evaluation of the implementation of the IT governance is made by using  index.KAMI Methode  which is an adoption of ISO/IEC 27001, which is a tool to analyze the readiness of the security level of information about an organization's security framework. The maturity of the implementation of the corporate governance of information technology within the Faculty of MIPA  UNPAK in  level two, which is still in the process of the effectiveness and consistency of application framework used. Keywords : Index KAMI, Maturity, Information Technolgy